The role of geospatial technology intelligence in efforts to prevent non-compliance of palm oil taxpayers - Bukit, Bollyazi Haru; Supriyadi, Adang; Subanidja, Steph; Prasetyono, Budi; Mado, Aloysius (Educoretax, 2025)
This study discusses the forms of threats, the role of intelligence and geospatial technology intelligence in efforts to prevent the threat of tax evasion in the palm oil sector related to data on area, age of plants and the reasonableness of plantation productivity by utilizing geospatial data. This study is a qualitative study with a descriptive design. The results of the study indicate that there is a form of threat of palm oil tax evasion mode related to the unreasonableness of turnover reporting based on data analysis of area, age of plants and the reasonableness of plantation productivity by utilizing geospatial data, and the role of BIN is needed to oversee the Palm Oil Governance Task Force, and the role of tax intelligence through geospatial data-based technology intelligence to prevent tax evasion mode related to the reasonableness of the area, age and productivity of plantations reported by taxpayers. It is hoped that this study can be an input for the Directorate General of Taxes to complete the tools for monitoring taxpayer compliance in the palm oil sector, so that it is in line with the objectives of the palm oil governance task force together with other government stakeholders who are interested in the palm oil business in Indonesia.